The components of abstracts: The logical structure of abstracts in the areas of materials science and technology and of library and information science - Jamar, Nina; Šauperl, Alenka; Bawden, David (New library world, 2014)
Purpose - The purpose of this study was to examine whether the logical structure of abstracts in the areas of materials science and technology and library and information science comply with the ISO 214 or IMRAD formats, while also suggesting guidelines for components of abstracts. Design/methodology/approach - In the first part of the research the components of abstracts are analysed. The results showed that not all the proposed structural elements are present in the abstracts. Therefore also the improved prototypes and recommended abstracts are developed to examine the satisfaction of readers with different forms of abstracts. According to the results of satisfaction of readers with different forms of abstracts, uniform guidelines for the components of abstracts in accordance with the IMRAD format are proposed. Findings - The introduction (I) should include three sentences of background information. The method (M) should include three sentences of method. The results (R) should include three sentences of results. The discussion (D) should include two sentences of conclusions. The conclusions should present the implications of the results on subjects that were not part of the study, suggestions for possible application of the findings, suggestions for further research work and an evaluation of the research. Originality/value - It is important to emphasize that even if the guidelines for writing abstracts by the individual journal exist, authors do not always take them into account. Therefore, it is important that the abstracts that are actually published in journals were analysed. It is also important that the opinion of researchers was taken into account.